Moss, Jordan. The Face of Evil. - Jarvis, Dale Gilbert, 1971- (2011)
Recording of a ghost story told by Jordan Moss, a Grade 9 student at Leary's Brook Junior High. Recorded in the Newman Wine Vaults Provincial Historic Site as part of the Young Folklorists Program run by the Heritage Foundation of Newfoundland and Labrador in May, 2011. Jordan writes, "My mother told me this story about how she was on her way to work and a nun looked at her and she had no face or feet."